Identification of maize inbreds for hybridization using agro-morphological traits and SSR markers through clustering and population structure analysis - Sneha S; SathyaSheela K.R.V; Ravikesavan R; Selvakumar T; BabuRajendraPrasad V; Sivakumar S; KumariVinothana N; Deepika V (Molecular Biology Reports, 2026)

Bioleaching assisted electrochemical reclamation of titanium from redmud using extremophilic Bacillus subtilis N3 - Punniyadharshini S; Unnamalai S; Sruthi K; Alagarsamy G; Manjima Sanil; Sankarganesh Jeyaraj; Prasana Manikanda Kartik J; Chandraraj K; Vinod Kumar Verma; Krishna Kumari V; Selvakumar R (Bioresource Technology Reports, 2025)

Accurate cadmium (II) detection with single crystalline α-Fe2O3 nano-hexagonal modified screen-printed carbon electrode - Selvakumar Palanisamy; Murugan Velmurugan; G. Bharath; Matteo Chiesa; Rajesh Madhu; Fedor V Kusmartsev; Sridharan Balu (Journal of Environmental Sciences, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

Genetic diversity and principal component analysis in Indian bean (Lablab purpureus var. typicus L.) genotypes under rainfed conditions of Western India - K. Gangadhara; L. P. Yadav; V. V. Appa Rao; A. K. Singh; A. K. Verma; Raman Selvakumar; Gograj Singh Jat (Genetic Resources and Crop Evolution, 2024)

Influencing factors and environmental feasibility analysis of agricultural waste preprocessing routes towards biofuel production – A review - Selvakumar Periyasamy; Adane Asefa Adego; P. Senthil Kumar; G.G. Desta; T. Zelalem; V. Karthik; J. Beula Isabel; Mani Jayakumar; Venkatesa Prabhu Sundramurthy; Gayathri Rangasamy (Biomass and Bioenergy, 2024)

Microplastic intrusion into the zooplankton, the base of the marine food chain: Evidence from the Arabian Sea, Indian Ocean - Prasun Goswami; Narasimman Selvakumar; Pankaj Verma; Mahua Saha; V. Suneel; Nambali Valsalan Vinithkumar; Gopal Dharani; Chayanika Rathore; Jibananand Nayak (Science of The Total Environment, 2023)

Recent advances in consolidated bioprocessing for conversion of lignocellulosic biomass into bioethanol – A review - Selvakumar Periyasamy; J. Beula Isabel; S. Kavitha; V. Karthik; Badr A. Mohamed; Desta Getachew Gizaw; P. Sivashanmugam; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Chemical, physical and biological methods to convert lignocellulosic waste into value-added products. A review - Selvakumar Periyasamy; V. Karthik; P. Senthil Kumar; J. Beula Isabel; Tatek Temesgen; B. M. Hunegnaw; B. B. Melese; Badr A. Mohamed; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Combined effect of nano-silica and randomly distributed fibers on the strength behavior of clay soil - P. Kulanthaivel; S. Selvakumar; B. Soundara; V. S. Kayalvizhi; S. Bhuvaneshwari (Nanotechnology for Environmental Engineering, 2022)

Graphene-based materials for environmental applications: a review - V. Karthik; P. Selvakumar; P. Senthil Kumar; Dai-Viet N. Vo; M. Gokulakrishnan; P. Keerthana; V. Tamil Elakkiya; R. Rajeswari (Environmental Chemistry Letters, 2021)

Enzyme-loaded nanoparticles for the degradation of wastewater contaminants: a review - V. Karthik; P. Senthil Kumar; Dai-Viet N. Vo; P. Selvakumar; M. Gokulakrishnan; P. Keerthana; V. Audilakshmi; J. Jeyanthi (Environmental Chemistry Letters, 2021)

Structure-based design, synthesis, biological evaluation, and molecular docking of novel 10-methoxy dibenzo[b,h][1,6]naphthyridinecarboxamides - K. N. Vennila; B. Selvakumar; V. Satish; D. Sunny; S. Madhuri; K. P. Elango (Medicinal Chemistry Research, 2021)

Biodegradation of phenolic resin used in leather processing by laccase producing Trichoderma aureoviridae - I. Lawrance; V. Sivaranjani; A. Michael Selvakumar; Yasmin Khambhaty; P. Saravanan (International Journal of Environmental Science and Technology, 2019)

Design, Synthesis, Spectral Analysis, In Vitro Anticancer Evaluation and Molecular Docking Studies of Some Fluorescent 4-Amino-2, 3-Dimethyl-1-Phenyl-3-Pyrazolin-5-One, Ampyrone Derivatives - D. Premnath; Israel V. M. V. Enoch; P. Mosae Selvakumar; M. Indiraleka; J. Jannet Vennila (Interdisciplinary Sciences: Computational Life Sciences, 2017)

A Highly Selective Fluorescent Sensor for Pb2+ Based on a Modified β-Cyclodextrin - Eva Janet Antony; Masilamani Raj; Rajathi Queen Paulpandi; Mosae Selvakumar Paulraj; Israel V. M. V. Enoch (Journal of Fluorescence, 2015)

In vitro propagation of the medicinal plant Plumbago zeylanica L. Through nodal explants - V. Selvakumar; P. R. Anbudurai; T. Balakumar (In Vitro Cellular & Developmental Biology - Plant, 2001)

Prevalence of neutralising antibodies to Berne virus in animals and humans in Vellore, South India - D. W. G. Brown; R. Selvakumar; D. J. Daniel; V. I. Mathan (Archives of Virology, 1988)